Cover Feature: Microscopic Insights on the Multiferroic Perovskite‐Like [CH3NH3][Co(COOH)3] Compound (Chem. Eur. J. 2/2018). Issue 2 (25th October 2017) - Mazzuca, Lidia; Cañadillas‐Delgado, Laura; Fabelo, Oscar; Rodríguez‐Velamazán, J. Alberto; Luzón, Javier; Vallcorba, Oriol; Simonet, Virginie; Colin, Claire V.; Rodríguez‐Carvajal, Juan
Abstract : The perovskite‐like metal‐organic compound [CH3 NH3 ][Co(COOH)3 ] shows a combination of long‐range magnetic order with a transition from paraelectric to antiferroelectric‐like states, making it a Type I multiferroic material. The nuclear phase transition and the magnetic structure have been studied combining synchrotron X‐ray measurements, neutron diffraction data and ab initio calculations. More information can be found in the Full Paper by L. Cañadillas‐Delgado, O. Fabelo et al. onpage 388 .